A survey of the Canadian strong motion seismograph network - Rogers, Garry C. (Canadian Geotechnical Journal, 1976)
At the end of 1974 there were 45 accelerographs and 75 seismoscopes deployed in Canada. The Department of Energy, Mines, and Resources and the National Research Council of Canada have installed most of the instruments but one quarter of them are privately owned. Three quarters of the instruments are located near the west coast with the next largest concentration in the St. Lawrence Valley region. There is one instrument in the Arctic. The majority have been deployed to measure ground motion in populated areas but a few have been deployed in areas of higher seismicity remote from population centers. In western Canada particular emphasis has been placed on measuring the response of different soil types and soil depths. The only major structures in the country that have been instrumented are two large dams.